Comparative Study of Thin-Film Perovskite Solar Cells Based on Methylammonium Lead Iodide and Methylammonium Lead Bromide - Farooq, W. (Praise Worthy Prize S.r.l, 2021)
Less efficient solar cells are a hindrance in the commercialization of thin-film solar cells (TFSCs). Perovskite materials have now been extensively studied as an innovative epoch candidate. They are considered a panacea in the field of photovoltaics, as they levitate the Power Conversion Efficiency (PCE) of the device with proper encapsulation of the materials. In this paper, the proffer structures are deliberately devised and reckon for optimizing the thickness of prototypical materials such as Methylammonium lead iodide (CH3 NH3 PbI3 ) and Methylammonium lead bromide (CH3 NH3 PbBr3 ) perovskite, as there is a dire need to extract high conversion efficiency with minimum losses. Moreover, to improve the extraction of electrons and suppress the recombination losses, three Electron Transport Layers (ETLs) were introduced, which help in maintaining the open-circuit voltage (Voc). In addition, this study signifies that the lead iodidebased perovskite structure was found to more efficient as compared to lead bromide. The numerically extracted results after optimizing the structure under Standard Testing Conditions (STC) delivered the highest Î· of 24.89 with short-circuit current density, Jsc=24.04 mA/cm2, open-circuit voltage, VOC =1.31 V and Fill factor, FF=86.76 with an optimum thickness of 580 nm. Moreover, this fact-finding study also throws light on the temperature of the device and discovered result markedly shows that high temperature deteriorates the Î· of the cell. Copyright Â© 2021 Praise Worthy Prize S.r.l.-All rights reserved. Â© 2021 Praise Worthy Prize S.r.l.-All rights reserved.